Find f(1); f(2); f(3); f(4) and f(5) if f(n) is defined recursively by f(0) = 3 and for n = 0; 1; 2 for: f(n+1)= f(n)^2 - 2f(n)-2
Follow Math Help Forum on Facebook and Google+
Originally Posted by orendacl Find f(1); f(2); f(3); f(4) and f(5) if f(n) is defined recursively by f(0) = 3 and for n = 0; 1; 2 for: f(n+1)= f(n)^2 - 2f(n)-2 In order to understand recursion, you must understand recursion. Nevertheless, note that: $\displaystyle f(0+1) = f(1) = f(0)^2 - 2f(0) - 2 = 3^2 - 2 (3) - 2 = 1$ $\displaystyle f(1+1) = f(2) = f(1)^2 - 2f(1) - 2 = 1^2 - 2 (1) - 2 = -3$ etc.
View Tag Cloud